Efeito de nanopartículas de sílica em plantas de milho (Zea mays L.) tratadas com a rizobactéria Streptomyces (CLV16) - Navarro, Andressa Negreiros Flores Pilati (2020)
Nanotechnology comprehend a broad range of areas and represents an innovative approach for food production and crop management in the modern agriculture. Maize is in third place in the world cereal production, being considered essential in food. Silicon (non-nutritive element) is absorbed by many plants and polymerized in amorphous silica structures, and incorporated into biological structures such as stem, leaves and roots. Nanoparticles present a high surface-volume ratio, with the size <100 nm. Rhizobacteria that promote plant growth, such as Sreptomyces, are used in the management of many agricultural crops due to their beneficial effects by releasing of substances that help against pathogens or mineral absorption. The aim of this work was to evaluate the NPSiO2 in maize plants and its interaction with the rhizobacteria Streptomyces (CLV16). The toxicity of NPSiO2 was determined through the evaluation of germination rate, plant growth and enzyme activity related to oxidative stress. The interaction with the bacteria was evaluated through in vitro tests and plant growth. According to the results, NPSiO2 does not affect the germination rate. NPSiO2 63 nm and 110 nm impaired the initial growth of seedling roots. However, this harmful effect was not observed in plants after 45 days of growth. NPSiO2 did not interfere the growth of the CLV16, regardless of nanoparticle size and concentration. The CLV16 promoted the growth of maize plants in a similar way to that observed when using only NPSiO2. When seeds were exposed to NPSiO2 220 nm, plant growth was reduced. Plants germinated from seeds treated with NPSiO2 110 nm showed an increment in root growth and fresh and dry shoot mass. Plants sprayed with NPSiO2 showed an increase in the activities of antioxidant enzymes, suggesting that these nanoparticles were plant stressors. However, plants sprayed with NPSiO2 presented an increment in shoot length and fresh root mass. Thus, NPSiO2 modulated the growth of maize plants, mainly when seeds were treated rather than leaves sprayed.